Institutional Identification and Organizational Citizenship Behavior of Uganda Hotels’ Staff: The Mediation Role of Organizational Virtuousness - Gukiina, Joshua; Ntayi, Joseph Mpeera; Balunywa, Waswa; Ahiauzu, Augustine (Journal of Organizational Psychology, 2018)
The purpose of the present paper is to demonstrate that institutional identification and organizational virtuousness are constructs of the social exchange theory and can explain the engagement in organizational citizenship behaviour of the Uganda hotels’ staff. In terms of methodology, contrary to current studies on organizational citizenship behaviour, this study adopted a mixed research design and its attendant characteristics so as to examine the extent to which institutional identification predicts organizational citizenship behaviour, taking organizational virtuousness as a mediator of the relationship. Regarding the study findings, institutional identification is a significant predictor of organizational citizenship behaviour of the Uganda hotels’ staff and organizational virtuousness partially mediates the relationship between institutional identification and organizational citizenship behaviour. As far as the study limitations and Implications are concerned, admittedly, the instruments that measured the key variables of the study i.e. organization citizenship behaviour, institutional identification and organizational virtuousness, were adapted to suit the Uganda hotel environment. The study was entirely cross sectional yet; behaviour unfolds gradually. Above all, we adopted a positivistic approach to research yet it is highly structured and little attention was paid to qualitative responses because; we only needed explanations for the quantitative results. With regard to originality or value, the paper proudly domesticates institutional identification and organizational virtuousness within the social exchange theory and it directly tested for the predictive relationship between institutional identification and organizational citizenship behaviour.